Preassessment for anaesthesia - Singh,S (CRC Press, 2018)
Set at the level between the definitive reference work and the clinical manual, Essentials of Clinical Pulmonology is an invaluable cornerstone for all pulmonologists whether trainees or experienced clinicians.